Effects of Super-Activated Platelet Lysate on Early Healing of Tooth Extraction Sockets in Rats - Guo X; Lu H; Liu C; Zhang Y; Bi L (Dove Medical Press, 2022)
Xiaorui Guo,1,2 Huiying Lu,3 Chunxiang Liu,3 Yi Zhang,3 Liangjia Bi1 1Department of Stomatology, The Fourth Affiliated Hospital, Harbin Medical University, Harbin, 150001, People's Republic of China; 2State Key Laboratory of Military Stomatology and National Clinical Research Center for Oral Diseases and Shaanxi Key Laboratory of Oral Diseases, Department of Operative Dentistry and Endodontics, School of Stomatology, The Fourth Military Medical University, Xi'an, People's Republic of China; 3National and Local Joint Stem Cell Research & Engineering Center for Aging Diseases, Tian Qing Stem Cell Co., Ltd, Harbin, 150028, People's Republic of ChinaCorrespondence: Liangjia Bi, Department of Stomatology, The Fourth Affiliated Hospital, Harbin Medical University, Harbin, 150001, People's Republic of China, Tel/Fax +86 451 82576565, Email biliangjia1963@163.comPurpose: To evaluate the effect of super-activated platelet lysate (sPL) on wound healing of tooth extraction sockets in rats.Methods: Rat models of the tooth extraction socket were established. Thirty-six rats were divided into control and sPL groups and sacrificed on days 7, 14, and 28 after tooth extraction. Bone formation in tooth extraction sockets were observed by microscopic computed tomography (micro-CT) and hematoxylin and eosin (HE) staining; osteoprotegerin (OPG), receptor activator of nuclear factor kappa-&Bgr; ligand (RANKL), interleukin 6(IL-6), and tumor necrosis factor-alpha (TNF-α) proteins were detected by immunohistochemistry; and chemokine and osteogenic gene expressions were detected by polymerase chain reaction (PCR).Results: sPL accelerated soft tissue wound healing in the extraction socket of rats. Micro-CT showed that the amount of bone formation and bone volume fraction were higher in the sPL group than the control 14 days after extraction. HE staining showed promotion of the formation of bony trabeculae by sPL in the apical third of the extraction socket 7 days after extraction and more mature and organized bony trabeculae in the sPL group than the control 14 days after extraction; mature bony trabeculae filling most of the fossa with lesser bone porosity in the socket in the sPL group than the control 28 days after extraction. Immunohistochemistry showed that sPL induced OPG expressions 7 and 14 days after tooth extraction but did not affect the RANKL expression while transiently promoting the IL-6 expression 7 days after extraction. PCR showed that sPL promoted chemokine expressions 7 and 14 days after extraction. The expressions of osteogenesis-related factors were higher in the sPL group than the control 7 and 28 days after extraction, while the opposite trend was observed 14 days after extraction.Conclusion: sPL has a transient pro-inflammatory effect and promotes soft tissue healing and bone formation during early wound healing of extraction sockets in rats.Keywords: sPL, blood product, wound healing, bone formation, cytokines